Peningkatan Kemampuan Mendesain Pembelajaran Matematika Berdiferensiasi dengan Media Pembelajaran Augmented Reality bagi Guru SMK di Kabupaten Lumajang - Fahmi Abdul Halim; *Devi Rahayu Agustin; Muhammad Ridho'i; Muhamad Rama Maulana Ibrahim; Kamaliatun Nafisah (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2023)
Community service plays a crucial role in improving the quality of education. This article documents the efforts of the community service team from Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Lumajang in improving the ability of Mathematics teachers in Vocational High Schools (SMK) in Lumajang district to design differentiated learning using Augmented Reality (AR) technology. This programme is a concrete example of collaboration between universities and education practitioners in an effort to improve the quality of education at the local level. STKIP PGRI Lumajang's PKM team organised a series of training and workshops for SMK Maths teachers, introducing them to the potential of AR technology in improving learning effectiveness. This article details the concrete steps taken by the PKM team and SMK teachers in implementing AR technology in Maths learning. In addition, the evaluation results of the programme are also presented to provide a better understanding of its positive impact on learning quality and students' interest in learning. This article is expected to provide guidance and inspiration for other educators, researchers, and education practitioners who want to develop innovative learning methods using AR technology. This kind of collaboration also illustrates the importance of knowledge sharing between academics and practitioners to create positive changes in the world of education.